2010
DOI: 10.1007/s10584-010-9896-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of uncertainties in the design of international water treaties: an historical perspective

Abstract: Water is one natural resource whose management is especially susceptible to uncertainties, many of which are being exasperated by climate change. Some of these uncertainties originate from knowledge deficits in physical conditions while others relate to behavioral and social variability related to water supply and use. However, to our knowledge no quantitative analysis of how uncertainties have been translated into transboundary water treaty structures exists. The present paper partially fills this gap through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…The authors enumerate several allocation mechanisms, which are echoed in a number of other studies (e.g. Gleick 1992;139;Wolf and Hamner, 2000;Drieschova, Fischhendler, and Giordano, 2011).…”
Section: Allocation Mechanism Designmentioning
confidence: 99%
“…The authors enumerate several allocation mechanisms, which are echoed in a number of other studies (e.g. Gleick 1992;139;Wolf and Hamner, 2000;Drieschova, Fischhendler, and Giordano, 2011).…”
Section: Allocation Mechanism Designmentioning
confidence: 99%
“…A paper examined 289 agreements signed between 1857 and 1999. As main results, it was identified that 60% of the documents cited some kind of uncertainty and risk (especially related to water flow, infrastructure and environment; Drieschova et al, 2011). It points out that there is already some previous guidance that supports a global pact directed to the mentioned approach.…”
Section: Scope 1: Risk As the Water Management Paradigmmentioning
confidence: 93%
“…Por supuesto, la gente rara vez se ajusta a un único conjunto de valores morales, y probablemente cualquier analista o diplomático recurriría a una serie de principios para los enfoques que aborden. Aún así, vale la pena indagar en la discrepancia en las investigaciones sobre el río Jordán -por tomar un caso extremo-que o bien se centran en intentar explicar la distribución asimétrica de agua entre los actores (por ejemplo, Messerschmid, 2011;Selby, 2013, p.19), o no la cuestionan en absoluto (por ejemplo, Drieschova et al, 2011;Feitelson y Rosenthal, 2012). Si bien la diferencia en el énfasis se puede atribuir en parte a matices y preferencias disciplinarias (Relaciones Internacionales, Geografía Política) y no se han investigado las corrientes de justicia preferidas por los autores, el punto es que un mismo acuerdo de aguas transfronterizas puede ser considerado como manifiestamente injusto desde una perspectiva, y "lo suficientemente justo" desde otra.…”
Section: Relaciones Internacionalesunclassified